2015
DOI: 10.4103/2152-7806.166887
|View full text |Cite
|
Sign up to set email alerts
|

Timing and prognosis of surgery for spinal epidural abscess: A review

Abstract: Background:The nonsurgical versus surgical management of spinal epidural abscesses (SEAs) remains controversial. Even with the best preoperative screening for multiple risk factors, high nonoperative failure rates are attended by considerable morbidity (e.g., irreversible paralysis) and mortality. Therefore, the focus remains on early surgery.Methods:Most papers promote early recognition of the clinical triad (e.g., fever [50%], spinal pain [92–100%], and neurological deficits [47%]) for SEA. They also identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 33 publications
(57 reference statements)
0
46
1
1
Order By: Relevance
“…In addition to antimicrobial therapy, prompt surgery is indicated in most cases of SEA [3, 8, 27, 40, 46, 47]. Successful treatment of SEA with medical therapy alone in selected patients has also been reported [27, 40, 46, 4851].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to antimicrobial therapy, prompt surgery is indicated in most cases of SEA [3, 8, 27, 40, 46, 47]. Successful treatment of SEA with medical therapy alone in selected patients has also been reported [27, 40, 46, 4851].…”
Section: Treatmentmentioning
confidence: 99%
“…However, caution is advised when interpreting these reports because of their observational nature and the potential for selection of less severely ill patients for medical therapy alone [3]. A recent review article concluded that most studies advocate for early (within 24 hours of diagnosis) surgery due to high failure rates and a significant risk of morbidity (22% for permanent paralysis) and mortality (3% to 25%) with nonoperative treatment alone [47]. In contrast, medical therapy alone may be favored in patients with panspinal SEA involvement or those with complete paresis for 72 hours or more or when surgery is deemed too risky [3, 15, 40, 46].…”
Section: Treatmentmentioning
confidence: 99%
“…As discussed, by Epstein et. al in a recent review, there is a high rate of failure (10-management alone4 . While it may seem reasonable to consider initial medical management for the neurologically intact patient, the high rates of treatment failure with both neurological progression and need for surgical intervention are an important discussion point to be included in any informed consent conversation.Kim and coworkers12 looked specifically at risk factors for antibiotic failure and found that diabetic patients over 65 years of age with methicillin-resistant Staphylococcus aureus have a 99% likelihood of failing medical management, raising important pause as to whether such strategy should even be implemented.…”
mentioning
confidence: 97%
“…This is an important clinical concern because epidural abscess in spondylodiscitis -if not accurately treated -accounts for significant morbidity (e. g. persisting neurological deficits) and mortality rates [21]. The ongoing discussion about the early surgical treatment of epidural abscesses is an indication of its clinical impact [21 -23].…”
Section: Discussionmentioning
confidence: 99%